Comparison of the Efficacy of Short-Term and Long-Term Azithromycin Regimen with Metronidazole and Amoxicillin for Treatment of Moderate Chronic Periodontitis in Adults - Jenabian, Niloofar; Moghadamnia, Ali-Akbar; Abdollahi, Yalda; Kiakojouri, Amir (Journal of Dental School, 2020)
Objective: Administration of amoxicillin and metronidazole along with scaling and root planning (SRP) is an effective adjunctive therapy for chronic periodontitis. Studies have shown that administration of azithromycin is also effective for treatment of chronic periodontitis. This study aimed to compare the effect of short-term and long-term azithromycin regimen with amoxicillin and metronidazole for treatment of moderate chronic periodontitis in adults. Methods: This experimental study was carried out on 75 patients with moderate chronic periodontitis aged 35-50 yrs. with at least one pocket with a probing depth of 4-6 mm and attachment loss of 3-4 mm in each quadrant. Loe and Silness Gingival Index (GI), Modified Papillary Bleeding Index (MPBI) of Barnett, Loe and Silness Plaque Index (PLI), Probing Pocket Depth (PPD) and Attachment Loss (AL) were calculated at 0, 2 and 4 days, 6 weeks and 2 and 3 months after therapy. The patients underwent SRP and assigned to three groups. Group one received 250 mg metronidazole plus 250 mg amoxicillin 3 times a day for 7 days. Group 2 received 500 mg azithromycin twice daily for 7 days and group 3 received 250 mg azithromycin once a day for one month. Data were analyzed using ANOVA and Repeated Measures ANOVA. Results: PLI, MPBI, GI, PPD and AL parameters showed a significant reduction in all groups at all understudy time points (p<0.05). The reduction in BI, GI and PLI parameters was greater in group 3 compared to groups 1 and 2 (p <0.05); but, no significant difference was observed between groups 1 and 2 in this respect. A greater reduction in PPD was noted in groups 2 and 3 compared to group 1 (p<0.05). AL showed a significant reduction in group 3 compared to groups 1 and 2 only in the final follow-up session (p =0.042). Conclusion: Antibiotic therapy regimens were all effective for treatment of chronic periodontitis but the magnitude of improvement was greater in long-term azithromycin group compared to others.